2015
DOI: 10.1007/s00429-015-1097-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter structure and information processing speed in healthy older age

Abstract: Cognitive decline, especially the slowing of information processing speed, is associated with normal ageing. This decline may be due to brain cortico-cortical disconnection caused by age-related white matter deterioration. We present results from a large, narrow age range cohort of generally healthy, community-dwelling subjects in their seventies who also had their cognitive ability tested in youth (age 11 years). We investigate associations between older age brain white matter structure, several measures of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
58
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 49 publications
(63 reference statements)
12
58
0
4
Order By: Relevance
“…This domain represents efficiency of overall cognition measured by timing of performances. A decline in information processing speed during aging was associated with global white matter changes (Kuznetsova et al, ), and with fractional anisotropy alterations in the corpus callosum, superior longitudinal fasciculus and the inferior fronto‐occipital fasciculus (Kerchner et al, ). In stroke, decline of information processing speed was associated with cortical lesions in the left supramarginal and angular gyri and with the superior longitudinal fasciculus (Turken et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This domain represents efficiency of overall cognition measured by timing of performances. A decline in information processing speed during aging was associated with global white matter changes (Kuznetsova et al, ), and with fractional anisotropy alterations in the corpus callosum, superior longitudinal fasciculus and the inferior fronto‐occipital fasciculus (Kerchner et al, ). In stroke, decline of information processing speed was associated with cortical lesions in the left supramarginal and angular gyri and with the superior longitudinal fasciculus (Turken et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research found that average daily blood pressure (a modifiable risk factor) is associated with the progression of cerebrovascular disease and with declines in executive functioning and processing speed in older adults . Other research shows a connection between white matter integrity—as measured by diffusion tensor MRI—and processing speed among older adults . Thus, improving cardiovascular functioning—e.g., via lifestyle interventions and medication—could improve white matter health, and in turn, improve processing speed.…”
Section: Discussionmentioning
confidence: 99%
“…A higher DSST score indicates faster processing speed. Several studies using DSST to assess processing speed have been published elsewhere …”
Section: Methodsmentioning
confidence: 99%